Persepsi Masyarakat Terhadap Kinerja Wali Kota Medan Periode 2020 – 2024 - Ronaldo Supratman Silaban; Putri Apriani Harahap; Anna Maudina Manurung; Julia Ivanna (Jurnal Kewarganegaraan, 2023)
Abstract Public welfare is the goal of a country. The birth of regional autonomy gives regional governments the right and authority to manage their own regions with the aim of improving the welfare of the people. Regional Autonomy is the right, authority and obligation of autonomous regions to regulate and manage their own Government Affairs and the interests of local communities within the system of the Unitary State of the Republic of Indonesia. This research uses qualitative research with a case study approach. With the implementation of regional autonomy, the perception of the people of Medan City towards the performance of the Mayor of Medan has given rise to pros and cons. This can be seen from the effects felt by the community in accordance with the policies made by the Medan City government. Keywords: Community perception, Medan Mayor's performance, Regional autonomy Abstrak Kesejahteraan masyarakat merupakan tujuan suatu negara. Dengan lahirnya otonomi daerah memberikan hak dan wewenang pemerintah daerah untuk mengelolah daerahnya sendiri dengan tujuan untuk mensejahterakan rakyat. Otonomi Daerah adalah hak, wewenang, dan kewajiban daerah otonom untuk mengatur dan mengurus sendiri Urusan Pemerintahan dan kepentingan masyarakat setempat dalam sistem Negara Kesatuan Republik Indonesia. Penelitian ini menggunakan penelitian kualitatif dengan pendekatan studi kasus. Dengan penerapan otonomi daerah, persepsi masyarakat Kota Medan terhadap kinerja Wali Kota Medan menimbulkan pro dan kontrak hal ini dapat di lihat dari efek yang di rasakan masyarakat sesuai dengan kebijakan yang di buat pemerintah Kota Medan. Kata Kunci: Persespsi masyarakat, Kinerja Wali Kota Medan, Otonomi daerah